Heterorhabditis bacteriophora pampean-strain VEli (Nematoda): identification and pathogenicity against the strawberry pest Lobiopa insularis (Coleoptera: Nitidulidae) - Eliceche, Daiana Pamela (2017)
The pampean region in the Buenos Aires province of Argentina is a major horticultural area. Biological pesticides to control pest insects available in the market are scarce in this country and nonexistent based on entomonematodes. In this paper, we characterized a native entomopathogenic nematode isolated from soil in the pampas, and evaluated its infectivity and reproductive capacity in the strawberry sap beetle Lobiopa insularis. Morphological and molecular-genetic analysis determined this isolate to be a nematode of Heterorhabditis bacteriophora, thereafter designated as the VEli strain. A 901-bp genomic-DNA fragment was isolated (GenBank Accesion No KJ575524). The new strain was pathogenic against L. insularis. In 200 ml containers with autoclaved clay soil (100 ml), at concentrations of 1,000; 5,000 and 10, 000 IJs, mortality in larvae ranged from 25 to 77 %. At a concentration of 10,000 IJs, infectivity was higher in larvae and pupae (77 ± 20% and 64 ± 25 %, respectively) than in adults (2.2 ± 1.1 %). The lethal concentration required to kill 50 and 90 % of the larvae (LC50 and LC90) over 10 days was 2,840 and 23,743 IJs. Differences were observed in the parasitism levels and emergence time of IJs between concentrations and stages, although not for production. Heterorhabditis bacteriophora strain VEli is the first entomopathogenic nematode found to infect and kill L. insularis, capable of completing its life cycle in all strawberry sap beetle stages. This availability would enable the establishment and subsequent dispersal of the strain in strawberry fields. Finally, this report constitutes the first presentation of data on the morphological, morphometric, and molecular-genetic characterization of a native entomopathogenic nematode strain from the Buenos Aires province, Argentina.